The Impact of Glycemic Control and Variability (HbA1c) on the Rate of Glomerular Filtration Rate Decline in Diabetes Mellitus: A Systematic Review - Cut Lisa Afrianna; Irmayani; T Iskandar Rizal (International Medical Journal Corp. Ltd, 2025)
Introduction: Diabetic Kidney Disease (DKD) is a leading cause of end-stage renal disease (ESRD) globally. While mean glycated hemoglobin (HbA1c) is an established risk factor for DKD progression, the impact of long-term glycemic variability remains less clearly synthesized. This review systematically evaluates the association of both mean HbA1c and HbA1c variability with the rate of glomerular filtration rate (GFR) decline in individuals with type 1 (T1DM) and type 2 diabetes (T2DM). Methods: A systematic search of PubMed, Embase, Web of Science, and the Cochrane Library was conducted for longitudinal cohort studies published up to March 2024. Studies were included if they reported on mean HbA1c or long-term HbA1c variability (measured by standard deviation, coefficient of variation [CV], or variability score) and the primary outcome of GFR decline. The methodological quality of included studies was assessed using the Cochrane ROBINS-I tool for non-randomized studies. Results: A total of 16 longitudinal studies met the inclusion criteria. The findings consistently demonstrated that both higher mean HbA1c and greater HbA1c variability were significantly and independently associated with a more rapid decline in GFR. A